An evaluation of artificial intelligence study assistant on learning motivation and self-efficacy in undergraduate dental students of private university in Surabaya: A pilot study - Agrippine Putricia Asaeli; Jennifer Widjaja; Natalya Indayani (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Artificial Intelligence (AI) study assistants are increasingly used in undergraduate dental education; however, evidence regarding their impact on learning motivation and self-efficacy remains limited. Purpose: to evaluate the use of AI study assistants on learning motivation and self-efficacy among undergraduate dental students. Methods: A cross-sectional survey was conducted among undergraduate dental students using a structured, self-administered questionnaire. The survey assessed AI usage patterns, learning motivation, self-efficacy related to clinical reasoning and preclinical learning, and perceptions of usefulness, trust, and behavioural intention. Responses were recorded using Likert-scale items and analysed. Results: 35 respondents (100%) reported prior use of AI study assistants, with over 90% indicating frequent use (often or daily). Most students agreed that AI tools increased motivation to study dental subjects, supported more consistent preparation for classes and examinations, and enhanced interest in learning. Our findings suggest that respondents who reported using AI also showed higher perceived self-efficacy in basic clinical reasoning, application of theoretical knowledge to preclinical tasks, and identification of errors. While students generally trusted AI feedback and intended to continue using these tools, some expressed uncertainty regarding confidence in performing clinical tasks independently and concerns about the accuracy of AI-generated information. Conclusion: AI study assistants were widely used and positively perceived by undergraduate dental students, with beneficial effects on learning motivation and perceived self-efficacy. However, AI tools should be integrated as supportive adjuncts rather than replacements for hands-on training and educator guidance. Structured implementation and AI literacy education may help optimize their role in dental education. .